2015
DOI: 10.2319/100714-717.1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of human osteoblast proliferation and morphology on orthodontic mini-implants

Abstract: Osteoblast proliferation was present on the mini-implants studied, which increased over time; however, no significant difference between brands was observed. No difference was seen between the mini-implants evaluated in terms of chemical composition. Cell adhesion after 72 hours suggests that areas of bone remodeling can be achieved, thus initiating the process of mini-implant anchorage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Although several studies are available in the literature regarding the biocompatibility and potential cytotoxic impact of the metal ions released from implants [21][22][23], restorations [24][25][26] and orthodontic appliances such as Fe, Ni, Cr, Co, Ti, and Mo [27][28][29], no previous report has simulated orthodontic alloys with metal ion mixtures to evaluate their potential. Cultured animal or human cell lines such as fibroblasts [28] and osteoblasts [30] have been mainly used to evaluate the cytotoxic effect of orthodontic appliances, and currently, only a few studies [31,32] have included yeast for these type of studies. Limberger et al [31] compared the results on S. cerevisiae with other cell lines and concluded that microorganisms are a reliable model for cytotoxic testing of orthodontic materials.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies are available in the literature regarding the biocompatibility and potential cytotoxic impact of the metal ions released from implants [21][22][23], restorations [24][25][26] and orthodontic appliances such as Fe, Ni, Cr, Co, Ti, and Mo [27][28][29], no previous report has simulated orthodontic alloys with metal ion mixtures to evaluate their potential. Cultured animal or human cell lines such as fibroblasts [28] and osteoblasts [30] have been mainly used to evaluate the cytotoxic effect of orthodontic appliances, and currently, only a few studies [31,32] have included yeast for these type of studies. Limberger et al [31] compared the results on S. cerevisiae with other cell lines and concluded that microorganisms are a reliable model for cytotoxic testing of orthodontic materials.…”
Section: Discussionmentioning
confidence: 99%
“…Bueno & Basting evaluated the influence of Ti alloy mini-implants on osteoblasts and concluded that their proliferation has increased from 24 to 72 hours. Also, cell adhesion at 72 hours suggested the presence of bone remodeling, required for osseointegration initiation [ 22 ]. Malkoҫ et al studied the cytotoxicity in five types of mini-implants made from two different alloys (stainless steel and Ti alloy) using a real-time cell analysis system.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Mini-screws became widely used to bear orthodontic and orthopaedic loads, becoming effective orthodontic anchorage devices [34][35]. Firstly, the material of choice to manufacture mini-implants was commercially pure Titanium (cp Ti), but in order to improve its mechanical properties, some elements such as aluminum (Al), vanadium (V) and iron (Fe) have been incorporated [36]. Many new systems were introduced, such as onplants [37], palatal implants [38], bicortical screws [39], miniplates [40], miniplates with a tube [41], and the zygoma anchorage system [42].…”
Section: Introductionmentioning
confidence: 99%